2017
DOI: 10.1177/0003702817691288
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Ablation Sampling for Accurate Analysis of Sulfur in Edible Salts

Abstract: We evaluated the performance of laser ablation analysis techniques such as laser-induced breakdown spectroscopy (LIBS), laser ablation inductively coupled optical emission spectrometry (LA-ICP-OES), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), in comparison with that of ICP-OES using aqueous solutions for the quantification of sulfur (S) in edible salts from different geographical origins. We found that the laser ablation based sampling techniques were not influenced by loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…LIBS is a superb technology to investigate biological specimens listed above and has also proven its capability in forensic science (Miziolek et al 2006;Cremers and Radziemski, 2006;Pasquini et al 2007;Singh and Thakur, 2007;Gondal et al, 2016d, Almessiere et al, 2018. The most recent biomedical LIBS applications have been condensed in Table 1 (Sinescu et al 2008;Negrutiu et al 2008;Hamzaoui et al 2011;Singh et al 2008Singh et al , 2009aPathak et al 2011;Jaswal et al, 2016a, b;Anzano and Lasheras 2009;Yueh et al 2009;El-Hussein et al 2010;Wu et al 2008;Martin et al 2003Martin et al , 2005Melikechi et al 2008;Lee et al 2017;Samek et al 1999;Riberdy et al 2017). Figure 2 shows different LIBS applications to analyze different kinds of bacterial samples, plant samples, animal and human tissues, and skin samples to map of metal elements in tissues and to analyze bio minerals.…”
Section: Biomedical Applications Of Libsmentioning
confidence: 99%
“…LIBS is a superb technology to investigate biological specimens listed above and has also proven its capability in forensic science (Miziolek et al 2006;Cremers and Radziemski, 2006;Pasquini et al 2007;Singh and Thakur, 2007;Gondal et al, 2016d, Almessiere et al, 2018. The most recent biomedical LIBS applications have been condensed in Table 1 (Sinescu et al 2008;Negrutiu et al 2008;Hamzaoui et al 2011;Singh et al 2008Singh et al , 2009aPathak et al 2011;Jaswal et al, 2016a, b;Anzano and Lasheras 2009;Yueh et al 2009;El-Hussein et al 2010;Wu et al 2008;Martin et al 2003Martin et al , 2005Melikechi et al 2008;Lee et al 2017;Samek et al 1999;Riberdy et al 2017). Figure 2 shows different LIBS applications to analyze different kinds of bacterial samples, plant samples, animal and human tissues, and skin samples to map of metal elements in tissues and to analyze bio minerals.…”
Section: Biomedical Applications Of Libsmentioning
confidence: 99%
“…The concentrations of Mg 2+ , K + , Ca 2+ , and SO 4 2− vary typically from ∼100 parts per million (ppm) to ∼3%, depending on the natural sources and production methods of the salts. [2][3][4][5][6][7] Thus, the corresponding elements were identified as effective variables for classifying edible salt products according to their types, provenances, and production methods. [6][7][8][9][10][11] Tastes of salts are strongly dependent on the concentrations of Mg 2+ , Ca 2+ , and K + .…”
Section: Introductionmentioning
confidence: 99%
“…19 Lee et al used laser ablation as a sampling method for accurate analysis of Sr in edible salts. 20 Rehan et al analyzed toxic and essential metals in rock and sea salts using LIBS. 9 Kim et al reported the downsized LIBS instrument for on-site analysis of edible salts.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al . used laser ablation as a sampling method for accurate analysis of Sr in edible salts 20 . Rehan et al .…”
Section: Introductionmentioning
confidence: 99%